2011
DOI: 10.1002/ccd.23334
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of periprocedural myocardial infarction following stent implantation: Comparison between first‐ and second‐generation drug‐eluting stents

Abstract: Using the revised ARC definition, we found no significant difference in PMI between first- and second-generation DES. Overall, PMI occurred in 4.75%, which is 58% lower than with use of the historical PMI definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Several previous studies have shown that PMI correlates with worse short‐term and long‐term clinical outcomes , while other studies showed no such relation . Previous studies have proposed several definitions of PMI, including the universal definition , the third universal definition and the SCAI definition .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that PMI correlates with worse short‐term and long‐term clinical outcomes , while other studies showed no such relation . Previous studies have proposed several definitions of PMI, including the universal definition , the third universal definition and the SCAI definition .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical for clinical practitioners to assess or find out a series of controllable factors or predictors for the occurrence of PMI, which could be useful to reduce the risk of PMI. Tandjung K found that number of implanted stents not stent type was associated with the incidence of PMI [ 9 ]. Prasad also confirmed that elevation of troponin T was not only associated with angiographic characteristics, but also provided long-term prognostic information [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited knowledge about the relation between coronary dominance patterns and the risk of various adverse clinical events that can occur following percutaneous coronary interventions (PCI) with contemporary drug-eluting stents (DES). The aim of this study was to investigate the prognostic value of left dominance in relation to post-PCI outcome -in particular the rate of periprocedural MI (PMI), which in current DES studies has the highest incidence of all adverse clinical events [5][6][7] . We performed the analyses in patients in the prospective, randomised TWENTE trial 5,8 , which assessed a population of PCI patients with broad inclusion and only few exclusion criteria, treated with second-generation DES 9 .…”
Section: Introductionmentioning
confidence: 99%